(untitled) (Journal of EAHIL, 2020)
This interview with the head of the World Health Organization’s Library Service took place in May 2020, at the height of the COVID-19 pandemic. The interview provides a snapshot of how COVID-19 has affected the library service in an organization which is at the centre of disseminating information and providing leadership during the pandemic. In the interview, various aspects of managing a library service during a pandemic are discussed, including: how the library copes with high demand; how they maintain a high-quality search and retrieval service; how they make use of partnerships; what are the emerging "lessons learned" for their service; and how they try to take care of their well-being.